2020
DOI: 10.1186/s12891-020-3111-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of single-level interbody fusion with different internal fixation rod materials: a finite element analysis

Abstract: Background: Lumbar spinal fusion with rigid spinal fixators as one of the high risk factors related to adjacentsegment failure. The purpose of this study is to investigate how the material properties of spinal fixation rods influence the biomechanical behavior at the instrumented and adjacent levels through the use of the finite element method. Methods: Five finite element models were constructed in our study to simulate the human spine pre-and postsurgery. For the four post-surgical models, the spines were im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Similarly, Nikkhoo et al demonstrated that there was no signi cant difference in the ROM of adjacent segments between the PEEK rod models and the intact models, and PEEK rods reduced the disc height loss, uid loss, and disc stresses of adjacent segments under cyclic loading compared with those of Ti rods [30]. Additionally, during exion, the increase in disc stresses at L3/4 was highest (29.7-39.0%), and this was similar to that reported by Hsieh et al (50%) [23]. In fact, the structural stiffness provided by both rigid and semi-rigid xation systems is signi cantly greater than that of the normal spinal unit, which further changes the ROM and IDP of adjacent segments [13,41].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similarly, Nikkhoo et al demonstrated that there was no signi cant difference in the ROM of adjacent segments between the PEEK rod models and the intact models, and PEEK rods reduced the disc height loss, uid loss, and disc stresses of adjacent segments under cyclic loading compared with those of Ti rods [30]. Additionally, during exion, the increase in disc stresses at L3/4 was highest (29.7-39.0%), and this was similar to that reported by Hsieh et al (50%) [23]. In fact, the structural stiffness provided by both rigid and semi-rigid xation systems is signi cantly greater than that of the normal spinal unit, which further changes the ROM and IDP of adjacent segments [13,41].…”
Section: Discussionsupporting
confidence: 83%
“…It is known that axial stiffness affects exion and extension, whereas lateral bending stiffness affects rotation and lateral bending [26]. Therefore, axial stiffness is mainly provided by the anterior column, while the posterior internal xation is important to bending stiffness [23,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Granular bone graft was used in both groups, and our previous study had showed that granular bone graft had a high fusion rate [ 31 ]. (3) Both groups used a posterior pedicle screw system to create a stable local mechanical environment, which was also beneficial for bone graft fusion [ 32 ].…”
Section: Discussionmentioning
confidence: 99%